Nanoporous Silica from the Spray Reaction of Metal Solution Microdroplets with Silicon Tetrachloride - H. Isobe; Y. Hattori; H. Kanoh; K. Yamamoto; K. Kaneko (Adsorption Science & Technology)
Nanopore formation in silica, in which nanoparticles of metal compounds were embedded, was studied using analytical techniques such as SEM, XRD, XRF, XPS and nitrogen adsorption. Such metal compound nanoparticles formed between primary silica particles, providing micropores and mesopores caused by the formation of Si—O—M bonds (M = Al, Ni). Acid treatment dissolved the metal compound nanoparticles and destroyed the Si—O—M bonds, thereby increasing the micropore volume. The mesopore volume of the aluminium system increased on acid treatment, whereas that of the nickel system decreased.